Peran Whistleblowing dalam Pencegahan Fraud Pengelolaan Dana Desa di Provinsi Jambi - Ratih Kusumastuti; Iskandar Sam; Derist Touriano (Magister Ilmu Akuntansi Universitas Jambi, 2023)
The purpose of this study is to describe and provide empirical evidence regarding the role of whistleblowing in preventing fraud in the management of Village Funds. This research is a quantitative descriptive study. Source of data used in this research is primary data. Data collection was carried out using a survey method in the form of a questionnaire. The population in this study are villages that receive Village Funds spread across 9 districts in Jambi Province. The sample used in this study used a purposive sampling technique in 18 villages spread over 9 regencies in Jambi Province. data analysis using Structural Equation Modeling (SEM). The results of the study prove that Whistleblowing has a significant positive effect on Fraud Prevention. Then, Financial Reporting Compliance has a positive effect on Fraud Prevention. The results of the Moderation Test prove that Morality is not a moderating variable for the whistleblowing relationship with Fraud Prevention.